A educação que constrói a agroecologia no Brasil: trajetórias de um vínculo histórico - Faria, Andréa Alice da Cunha (2017)
The present research is born of a perception built from a social practice and it is structured around a relational object, that is, a political-pedagogical link between Agroecology and Popular Education. An investigative approach to the object is carried out through a study of the historical process of constitution of the Brazilian agroecological movement, from the beginning of the 1980s to the beginning of the 2000s. For such intent, bibliographic references and primary sources are used, as are documents created along this process and interviews with people who, directly or indirectly, participated, of the same. The information obtained in this way was analyzed with the help of a reading key constructed in chapters 1 and 2, based on early Freirean formulations developed in the 1950s, when intense debate about the direction of Brazilian development encouraged fruitfulness (as it is still valid to date) theoretical formulations, including on education and its role on the development of the country. A narrative of the process of constitution of the Brazilian agroecological movement is presented around three historical moments identified here as spaces of germination, interaction dynamics, and expansion movements. They correspond to chapters 3, 4, and 5 of the present work, which through a dense description (GEERTZ, 2008) aim to identify, explain, and interpret meanings, meanings and the resignifications consistent with a conception of Popular Education. The results reveal the existence of an organic link between Agroecology and Popular Education of a political-pedagogical nature. From a political point of view, such a link is expressed through the protagonism of the popular subjects and by the resistance character present in the construction of development alternatives for the country. From a pedagogical point of view, through the preponderance of reality as the place of departure and arrival, of reflexive praxis and permanent search, as constituent elements of a social movement that builds an Agroecology in Brazil, while updating Popular Education.